Anticonvulsant and anxiolytic activity of the peptide fraction isolated from the venom of the social wasp Polybia paulista - do Couto, Lucianna Lopes (Medknow Publications & Media Pvt Ltd, 2012)
BACKGROUND: Arthropod venoms have attracted interest because they represent a source of neuroactive compounds that can be useful tools in neuroscience and pharmacological investigations. OBJECTIVE: The purpose of the present work was to evaluate the anticonvulsant, anxiolytic, and behavioral effects of the peptide fraction separated from venom of the social wasp. MATERIALS AND METHODS: The low- molecular-weight compounds of the venom were separated by ultrafiltration and the bioassays were performed to test anticonvulsant and anxiolytic effects, as well as alterations in the spontaneous behavior of the animals. RESULTS: Intracerebroventricular injections of the compounds induced dose-dependent anticonvulsant effects and a potent anxiolytic activity. Regarding behavioral effects, no significant differences were observed in relation to the saline control group. CONCLUSION: The low-molecular-weight compounds of the venom of Polybia paulista include neuroactive peptides that can be used as pharmacological resources for anticonvulsant and anxiolytic drug research.